Glue solution for copper-clad plate, preparation method of glue solution, copper-clad plate and preparation method of copper-clad plate

By using 4-aminobenzoate phthalene and core-shell particle toughening agent in the glue solution of copper clad plate, the problem of low peel strength of copper clad plate is solved, and its mechanical properties and stability are significantly improved.

CN119684752AActive Publication Date: 2025-03-25SHENZHEN ZHICHENG APPLICATION TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411851011.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing copper clad plate has a low peel strength, which limits its application in the field of electronic equipment assembly where reliability requirements are high.

Method used

By combining the use of 4-aminobenzoate phthalene and core-shell particle toughening agent, a glue solution for copper clad plate was prepared, which significantly enhanced the interface shear strength between the medium glass fiber and the resin and the peel strength between the resin and the copper foil.

Benefits of technology

It significantly improves the peel strength and overall mechanical properties of copper clad plate, enhances its stability during the assembly and use of electronic products, and reduces the risk of stratification caused by insufficient peel strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190584060000021
    Figure BDA0005190584060000021
  • Figure BDA0005190584060000051
    Figure BDA0005190584060000051
  • Figure BDA0005190584060000061
    Figure BDA0005190584060000061
Patent Text Reader

Abstract

The invention provides a glue solution for a copper-clad plate, a preparation method of the glue solution, the copper-clad plate and a preparation method of the copper-clad plate, and belongs to the technical field of copper-clad plates. The glue solution for the copper-clad plate is prepared from the following components in parts by weight: 100 parts of matrix resin, 2 to 50 parts of a curing agent, 0 to 2 parts of an accelerant, 0 to 40 parts of filler, 50 to 130 parts of a solvent, 5 to 15 parts of 4-aminobenzoic acid phenolic ester phthalonitrile and 5 to 15 parts of core-shell particles. According to the glue solution for the copper-clad plate, through compound use of the 4-aminobenzoic acid phenolic ester phthalonitrile and the core-shell particle toughening agent, the interfacial shear strength of glass fibers and resin in the copper-clad plate, the peel strength of the resin and a copper foil and other key mechanical properties can be remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper clad laminates, and in particular relates to an adhesive for copper clad laminates and a preparation method thereof, a copper clad laminate and a preparation method thereof. Background Art

[0002] Copper clad laminates are widely used because of their good heat resistance and flame retardancy. However, in actual use, their peel strength often needs to be improved to meet higher requirements for electronic equipment assembly and other application scenarios. At present, in the preparation process of traditional copper clad laminates, due to factors such as the characteristics of raw materials and the setting of process parameters, the peel strength between the board and the copper foil is prone to low, which to a certain extent limits its application in fields with high reliability requirements.

[0003] CN108263068A discloses a method for preparing copper-clad laminates using a polyphenylene ether resin composition, which fully combines the excellent properties of low-molecular polyphenylene ether, cyanate ester, active ester, low-dielectric epoxy resin and multifunctional epoxy resin, and adjusts their respective ratios to prepare copper-clad laminates with relatively excellent dielectric properties and heat resistance, as well as good processability. However, its peel strength is only about 1.3N / mm, which needs to be further improved. Summary of the invention

[0004] In order to solve the problem of low peel strength of existing copper clad laminates, the present invention provides an adhesive for copper clad laminates and a preparation method thereof, a copper clad laminate and a preparation method thereof. The adhesive for copper clad laminates can significantly enhance the key mechanical properties of the copper clad laminates, such as the interface shear strength between the glass fiber and the resin, and the peel strength between the resin and the copper foil, by composite use of 4-aminobenzoic acid phenol ester phthalonitrile and a core-shell particle toughening agent.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a glue for copper clad laminates, which comprises the following components in parts by weight:

[0007] Main resin: 100 parts,

[0008] Curing agent: 2-50 parts,

[0009] Accelerator: 0-2 parts,

[0010] Filler: 0-40 parts,

[0011] 4-aminobenzoic acid phenol ester phthalonitrile: 5-15 parts,

[0012] Core-shell particles: 5 to 15 parts.

[0013] In a specific embodiment, the 4-aminobenzoic acid phenol ester phthalonitrile includes at least one of 4-aminobenzoic acid phenol ester phthalonitrile, 4-aminobenzoic acid biphenol ester phthalonitrile and 4-aminobenzoic acid bisphenol A type phthalonitrile.

[0014] The structural formulas of 4-aminobenzoic acid phenol ester phthalonitrile, 4-aminobenzoic acid biphenol ester phthalonitrile and 4-aminobenzoic acid bisphenol A type phthalonitrile are shown in formula (I) to formula (III):

[0015]

[0016] Wherein, R1 is any one of -H, -CH3, -OCH3, R2 is any one of -H, -CH3, -OCH3, X is any one of -CH2-, -S-, -SO2-, -C(CH3)2-, -C(CF3)2-. R1 and R2 are specifically at the ortho position or the meta position.

[0017] These compounds can be used alone or in combination, depending on the specific application scenarios, such as differences in temperature resistance requirements, dielectric loss, etc.

[0018] In a specific embodiment, the core-shell particles include at least one of a structure of methyl methacrylate-acrylonitrile copolymer as a shell and butadiene-styrene copolymer as a core, a structure of polybutyl acrylate copolymer as a core and acrylonitrile-styrene copolymer as a shell, a structure of polymethyl methacrylate as a shell and polybutyl acrylate as a core, a structure of polymethyl methacrylate as a shell and butadiene rubber as a core, and a structure of polymethyl methacrylate as a shell and silica as a core.

[0019] This type of core-shell structure enables the core-shell particles to exert a unique synergistic effect in the glue system, effectively dispersing stress and improving the peel strength of the material through the action between different phase interfaces.

[0020] In a specific embodiment, the main resin includes at least one of bisphenol A epoxy resin, brominated bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, and brominated phenol epoxy resin;

[0021] The curing agent includes at least one of dicyandiamide, dimethyl diphenyl sulfone, boron trifluoride monoethylamine, linear phenolic resin, and nitrogen-containing phenolic resin;

[0022] The accelerator includes at least one of 2-methylimidazole, 2-phenylimidazole, 2-phenyl, 4-methylimidazole, benzyldimethylamine, and 2-methyl-4-ethylimidazole;

[0023] The filler includes at least one of silicon dioxide, hollow ceramic microspheres, aluminum hydroxide, magnesium hydroxide, aluminum oxide and talc.

[0024] Different fillers can be selected in a targeted manner according to the specific performance requirements of the required product. For example, silicon dioxide can improve the insulation and heat resistance of the copper clad laminate; hollow ceramic microbeads can reduce the dielectric constant; aluminum hydroxide and magnesium hydroxide have flame retardant effects, etc. By reasonably matching fillers, the comprehensive performance of the copper clad laminate can be optimized.

[0025] In a specific embodiment, the invention further comprises: a solvent: 60 to 120 parts.

[0026] In a specific embodiment, the solvent includes at least one of dimethylformamide, acetone, butanone, toluene, xylene, propylene glycol methyl ether, ethylene glycol methyl ether, and cyclohexanone.

[0027] Different solvents can be selected based on the performance requirements of the desired product, such as matching the solubility properties of the curing agent.

[0028] The present invention also provides a method for preparing a glue solution for copper clad laminates, comprising the following steps:

[0029] First, use a solvent with a mass of 5 to 10 times that of the curing agent to dissolve the curing agent; then add 4-aminobenzoic acid phenol ester phthalonitrile and core-shell particles to the remaining solvent, and stir to mix at 45 to 60° C.; then mix with the main resin, and stir at high speed for 20 to 60 minutes until it is uniform; continue to add the dissolved curing agent, and stir to make it uniformly mixed; then add the filler, and stir at high speed emulsification for 30 to 60 minutes until it is uniform; finally, add the accelerator, and stir at high speed emulsification for 20 to 60 minutes until it is uniform; after maintaining high-speed shear emulsification stirring and maturing for 5 to 10 hours, the preparation is completed.

[0030] The high-speed stirring speed is 1500-3000RPM, the high-speed shear emulsification stirring speed is 1500-3000RPM, and the speed in the specific embodiments can be 2000RPM.

[0031] The present invention also provides a method for preparing a copper clad laminate, comprising the following steps:

[0032] The above-mentioned adhesive liquid is applied on the glass fiber cloth to form an adhesive layer with uniform thickness, and then dried to evaporate the solvent in the adhesive liquid to form a prepreg. The prepreg is then compounded with copper foil and pressed to prepare a copper clad laminate.

[0033] In one embodiment, the gluing is performed at 180-210°C at a speed of 10-30 m / min; the pressing is performed at a pressure of 25-35 kg / cm 2 , press at a temperature of 170-190°C for 60-120 minutes.

[0034] The present invention also provides a copper clad plate, which is prepared by the above-mentioned preparation method.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) Optimization of interface properties: The synergistic effect of 4-aminobenzoic acid phenol ester phthalonitrile and core-shell particle toughening agent greatly improves the interfacial compatibility and bonding strength between glass fiber and resin. The presence of amino groups on 4-aminobenzoic acid phenol ester phthalonitrile can improve the wettability of epoxy resin to glass fiber cloth. The surface of glass fiber cloth usually has a certain polarity, and the polarity of amino groups enables it to have a strong interaction with the surface of glass fiber cloth, promoting epoxy resin to better wet the glass fiber cloth, allowing epoxy resin to fully penetrate into the pores and fibers of the glass fiber cloth, increasing the contact area, and thus improving the interfacial bonding strength. At the same time, amino groups can also be adsorbed on the surface of glass fiber cloth to form an interfacial transition layer, which enhances the bonding between glass fiber cloth and epoxy resin.

[0037] (2) At the same time, the special core-shell structure of the core-shell particles enables them to act as a "bridge" at the interface, further promoting the interaction between the glass fiber and the resin, and effectively reducing interface defects and stress concentration points. This optimization of interface performance significantly improves the interface shear strength, allowing the glass fiber and the resin to work better together when the copper clad laminate is subjected to external forces, making it less likely for interface debonding to occur, thereby greatly improving the overall mechanical properties and reliability of the copper clad laminate.

[0038] (3) Improved peel strength: 4-aminobenzoic acid phenol ester phthalonitrile contains amino and cyano groups. Among them, the amino group undergoes a ring-opening reaction with the epoxy group of the epoxy resin to form a covalent bond connection, which increases the cross-linking density between the molecular chains, improves the cohesive strength of the epoxy resin, and can better resist the separation at the interface under the action of external forces, thereby improving the peel strength. The cyano group is a strong polar group that increases the rigidity of the molecular chain, improves the strength and hardness of the epoxy resin, and the intermolecular force between the cyano groups (such as dipole-dipole interaction) enhances the cohesive strength, which is conducive to improving the peel strength. The core-shell particle toughening agent effectively disperses the stress generated during the peeling process through its dispersion and stress transfer effect in the resin matrix, avoiding local peeling caused by stress concentration. The synergistic effect of the two significantly enhances the bonding force between the resin and the copper foil, greatly improves the stability of the copper clad laminate during the assembly and use of electronic products, reduces the risk of delamination caused by insufficient peel strength, and extends the service life of electronic products. DETAILED DESCRIPTION

[0039] The present invention is further described below with specific examples, but the embodiments of the present invention are not limited thereto.

[0040] Example 1

[0041] Glue formula

[0042] Main resin (brominated bisphenol A epoxy resin) 100g, curing agent (dicyandiamide) 3g, accelerator (benzyl dimethylamine) 0.2g, 4-aminobenzoic acid phenol ester phthalonitrile 8g, core-shell particle toughening agent (methyl methacrylate-acrylonitrile copolymer as shell, butadiene-styrene copolymer as core structure) 5g, solvent (dimethylformamide 50g, acetone 20g). The structural formula of 4-aminobenzoic acid phenol ester phthalonitrile in this embodiment is shown in formula (IV):

[0043]

[0044] R1 is -CH3.

[0045] Preparation method:

[0046] Preparation of glue

[0047] Use a solvent (dimethylformamide) with a mass of 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; then in another container, add 4-aminobenzoic acid phenol ester phthalonitrile and core-shell particle toughening agent (methyl methacrylate-acrylonitrile copolymer as the shell, butadiene-styrene copolymer as the core structure) to the remaining mixed solvent of dimethylformamide and acetone at a temperature of 60°C, and stir at high speed for 30 minutes to mix them evenly. This part becomes mixed liquid ①; add mixed liquid ① to the main resin reactor and stir at high speed for 20 minutes until it is uniform; continue to add the dissolved curing agent (dicyandiamide) and stir at high speed for 20 minutes until it is uniform. Add the accelerator (benzyl dimethylamine) and stir at high speed emulsification for 60 minutes until it is uniform. After maintaining high-speed shear emulsification stirring and maturing for 6 hours, the preparation is completed.

[0048] Gluing and lamination

[0049] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0050] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0051] Example 2

[0052] Glue formula

[0053] Main resin (brominated bisphenol A epoxy resin) 100g, curing agent (dicyandiamide) 2.7g, accelerator (benzyl dimethylamine) 0.2g, accelerator (2-methylimidazole) 0.05g, 4-aminobenzoic acid biphenyl ester phthalonitrile 10g, core-shell particle toughening agent (with polymethyl methacrylate as shell and polybutyl acrylate as core structure) 5g, solvent (dimethylformamide 50g, butanone 20g). The structural formula of 4-aminobenzoic acid biphenyl ester phthalonitrile in this embodiment is shown in formula (V):

[0054]

[0055] R2 is -CH3.

[0056] Preparation method:

[0057] Preparation of glue

[0058] Use a solvent (dimethylformamide) with a mass of 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; then in another container, add 4-aminobenzoic acid diphenyl ester phthalonitrile and core-shell particle toughening agent (structure with polymethyl methacrylate as shell and polybutyl acrylate as core) to the remaining mixed solvent of dimethylformamide and butanone at a temperature of 60°C, and stir at high speed for 30 minutes to mix them evenly. This part becomes mixed liquid ①. Add mixed liquid ① to the main resin reactor and stir at high speed for 20 minutes until it is uniform. Continue to add the dissolved curing agent (dicyandiamide) and stir at high speed for 20 minutes until it is uniform. Add accelerator (benzyl dimethylamine) and accelerator (2-methylimidazole), and stir at high speed emulsification for 60 minutes until it is uniform. After maintaining high-speed shear emulsification stirring and maturing for 6 hours, the preparation is completed.

[0059] Gluing and lamination

[0060] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0061] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0062] Example 3

[0063] Glue formula

[0064] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (linear phenolic resin) 24g, accelerator (2-methyl-4-ethylimidazole) 0.08g, filler (aluminum hydroxide 10g, silicon dioxide 15g), 4-aminobenzoic acid bisphenol A type phthalonitrile 5g, core-shell particle toughening agent (polymethyl methacrylate as shell, silicon dioxide as core structure) 15g, solvent (dimethylformamide 50g, acetone 20g). 4-aminobenzoic acid bisphenol A type phthalonitrile has a structural formula as shown in formula (III), wherein X is -C(CH3)2-.

[0065] Preparation method:

[0066] Preparation of glue

[0067] Use a solvent (dimethylformamide) with a mass of 5 times that of the curing agent to dissolve the curing agent (linear phenolic resin). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; then in another container, add 4-aminobenzoic acid bisphenol A phthalonitrile and core-shell particle toughening agent (polymethyl methacrylate as shell, silica as core structure) to the remaining mixed solvent of dimethylformamide and acetone at 50°C, stir at high speed for 30 minutes to make it evenly mixed, this part becomes mixed liquid ①. Add the mixed liquid ① to the main resin reactor and stir at high speed for 20 minutes until it is uniform. Continue to add the dissolved curing agent (linear phenolic resin) and stir at high speed for 20 minutes until it is uniform. Add fillers (aluminum hydroxide and silica) and stir at high speed emulsification for 30 minutes until it is uniform. Finally, add the accelerator (2-methyl-4-ethylimidazole) and stir at high speed emulsification for 60 minutes until it is uniform. After keeping the high-speed shear emulsification stirring for 6 hours, the preparation is completed.

[0068] Gluing and lamination

[0069] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0070] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 190°C to prepare a copper clad laminate.

[0071] Comparative Example 1

[0072] Glue formula

[0073] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (dicyandiamide) 3g, accelerator (benzyldimethylamine) 0.2g, solvent (dimethylformamide 50g, acetone 20g).

[0074] Preparation method:

[0075] Preparation of glue

[0076] Use a solvent (dimethylformamide) with a mass 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; add the remaining solvents (dimethylformamide and acetone) and stir at high speed for 10 minutes until uniform. Add the dissolved curing agent (dicyandiamide) and stir at high speed for 20 minutes until uniform. Add the accelerator (benzyl dimethylamine) and stir at high speed for 60 minutes until uniform. After maintaining high-speed shear emulsification stirring for 6 hours, the preparation is complete.

[0077] Gluing and lamination

[0078] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0079] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0080] Comparative Example 2

[0081] Glue formula

[0082] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (dicyandiamide) 2.7g, accelerator (benzyldimethylamine) 0.2g, accelerator (2-methylimidazole) 0.05g, core-shell particle toughening agent (structure with polymethyl methacrylate as shell and polybutyl acrylate as core) 5g, solvent (dimethylformamide 50g, butanone 20g).

[0083] Preparation method:

[0084] Preparation of glue

[0085] Use a solvent (dimethylformamide) with a mass of 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor, and then add the core-shell particle toughener (structure with polymethyl methacrylate as the shell and polybutyl acrylate as the core) to the remaining mixed solvent of dimethylformamide and butanone at a temperature of 60°C in another container, and stir at high speed for 30 minutes to mix it evenly. This part becomes the mixed solution ①. Add the mixed solution ① to the main resin reactor and stir at high speed for 20 minutes until it is uniform. Continue to add the dissolved curing agent (dicyandiamide) and stir at high speed for 20 minutes until it is uniform. Add the accelerator (benzyl dimethylamine) and the accelerator (2-methylimidazole), and stir at high speed emulsification for 60 minutes until it is uniform. After maintaining high-speed shear emulsification stirring and maturing for 6 hours, the preparation is complete.

[0086] Gluing and lamination

[0087] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0088] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0089] Comparative Example 3

[0090] Glue formula

[0091] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (dicyandiamide) 2.7g, accelerator (benzyldimethylamine) 0.2g, accelerator (2-methylimidazole) 0.05g, 4-aminobenzoic acid diphenyl ester phthalonitrile (structural formula is the same as Example 2) 10g, solvent (dimethylformamide 50g, butanone 20g).

[0092] Preparation method:

[0093] Preparation of glue

[0094] Use a solvent (dimethylformamide) with a mass of 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; then in another container, add 4-aminobenzoic acid diphenyl ester phthalonitrile to the remaining mixed solvent of dimethylformamide and butanone at a temperature of 60°C, and stir at high speed for 30 minutes to mix them evenly. This part becomes the mixed solution ①. Add the mixed solution ① to the main resin reactor and stir at high speed for 20 minutes until it is uniform. Continue to add the dissolved curing agent (dicyandiamide) and stir at high speed for 20 minutes until it is uniform. Add the accelerator (benzyl dimethylamine) and the accelerator (2-methylimidazole), and stir at high speed emulsification for 60 minutes until it is uniform. After maintaining high-speed shear emulsification stirring and maturing for 6 hours, the preparation is complete.

[0095] Gluing and lamination

[0096] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0097] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0098] Comparative Example 4

[0099] Glue formula

[0100] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (dicyandiamide) 2.7g, accelerator (benzyldimethylamine) 0.2g, accelerator (2-methylimidazole) 0.05g, solvent (dimethylformamide 50g, butanone 20g).

[0101] Preparation method:

[0102] Preparation of glue

[0103] Use a solvent (dimethylformamide) with a mass 5 times that of the curing agent to dissolve the curing agent (dicyandiamide). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; add the remaining solvent (dimethylformamide and butanone), and stir at high speed for 10 minutes until uniform. Continue to add the dissolved curing agent (dicyandiamide), and stir at high speed for 20 minutes until uniform. Add the accelerator (benzyl dimethylamine) and the accelerator (2-methylimidazole), and stir at high speed for 60 minutes until uniform. After maintaining high-speed shear emulsification stirring for 6 hours, the preparation is complete.

[0104] Gluing and lamination

[0105] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0106] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 170°C to prepare a copper clad laminate.

[0107] Comparative Example 5

[0108] Glue formula

[0109] Main resin (brominated bisphenol A type epoxy resin) 100g, curing agent (linear phenolic resin) 24g, accelerator (2-methyl-4-ethylimidazole) 0.08g, filler (aluminum hydroxide 10g, silica 15g), solvent (dimethylformamide 50g, acetone 20g).

[0110] Preparation method:

[0111] Preparation of glue

[0112] Use a solvent (dimethylformamide) with a mass 5 times that of the curing agent to dissolve the curing agent (linear phenolic resin). Add the main resin (brominated bisphenol A epoxy resin) to the reactor; add the remaining solvent (dimethylformamide and acetone) and stir at high speed for 20 minutes until uniform. Continue to add the dissolved curing agent (linear phenolic resin) and stir at high speed for 20 minutes until uniform. Add fillers (aluminum hydroxide and silica) and stir at high speed for 30 minutes until uniform. Finally, add the accelerator (2-methyl-4-ethylimidazole) and stir at high speed for 60 minutes until uniform. After maintaining high-speed shear emulsification stirring for 6 hours, the preparation is complete.

[0113] Gluing and lamination

[0114] The prepared glue solution was applied to the glass fiber cloth through a glue coating machine in an oven at 190° C. at a speed of 20 m / min, with an RC of 54%, to prepare a semi-cured sheet.

[0115] After the six prepregs were laminated with the copper foil, they were placed in a laminator under a pressure of 30 kg / cm 2 , and pressed for 90 minutes at a temperature of 190°C to prepare a copper clad laminate.

[0116] Performance comparison:

[0117]

[0118] Micro-debonding method:

[0119] Test method: Install the fiber sample with the resin droplets fixed on the test machine so that the axis of the fiber is parallel to the loading direction of the test machine. Adjust the position of the tool or fixture so that it contacts the resin droplets. The fixture will apply shear force to the resin droplets, causing the resin droplets to gradually debond from the fiber surface. Record the maximum load, displacement and other data during the test, and observe the debonding process of the resin droplets.

[0120] Calculation of interfacial shear strength: Based on the data such as the maximum load, fiber diameter and length of the resin droplet recorded during the test, the interfacial shear strength is calculated using the formula. The calculation formula is τ = F / πdL, where τ is the interfacial shear strength, F is the maximum load, d is the fiber diameter, and L is the length of the resin droplet.

[0121] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.

Claims

1. A glue for copper clad laminate, characterized in that: In parts by weight, it includes the following components: Main resin: 100 parts, Curing agent: 2-50 parts, Accelerator: 0-2 parts, Filler: 0-40 parts, 4-aminobenzoic acid phenol ester phthalonitrile: 5-15 parts, Core-shell particles: 5 to 15 parts.

2. The adhesive for copper clad laminate according to claim 1, characterized in that: The 4-aminobenzoic acid phenol ester phthalonitrile includes at least one of 4-aminobenzoic acid phenol ester phthalonitrile, 4-aminobenzoic acid biphenol ester phthalonitrile and 4-aminobenzoic acid bisphenol A type phthalonitrile; The structural formulas of 4-aminobenzoic acid phenol ester phthalonitrile, 4-aminobenzoic acid biphenol ester phthalonitrile and 4-aminobenzoic acid bisphenol A type phthalonitrile are shown in formula (I) to formula (III): Wherein, R1 is any one of -H, -CH3, and -OCH3, R2 is any one of -H, -CH3, and -OCH3, and X is any one of -CH2-, -S-, -SO2-, -C(CH3)2-, and -C(CF3)2-.

3. The adhesive for copper clad laminate according to claim 1, characterized in that: The core-shell particles include at least one of a structure in which methyl methacrylate-acrylonitrile copolymer is the shell and butadiene-styrene copolymer is the core, a structure in which polybutyl acrylate copolymer is the core and acrylonitrile-styrene copolymer is the shell, a structure in which polymethyl methacrylate is the shell and polybutyl acrylate is the core, a structure in which polymethyl methacrylate is the shell and butadiene rubber is the core, and a structure in which polymethyl methacrylate is the shell and silica is the core.

4. The adhesive for copper clad laminate according to claim 1, characterized in that: The main resin includes at least one of bisphenol A epoxy resin, brominated bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, and brominated phenolic resin; the curing agent includes at least one of dicyandiamide, dimethyl diphenyl sulfone, boron trifluoride monoethylamine, linear phenolic resin, and nitrogen-containing phenolic resin; The accelerator includes at least one of 2-methylimidazole, 2-phenylimidazole, 2-phenyl, 4-methylimidazole, benzyldimethylamine, and 2-methyl-4-ethylimidazole; The filler includes at least one of silicon dioxide, hollow ceramic microspheres, aluminum hydroxide, magnesium hydroxide, aluminum oxide and talc.

5. The adhesive for copper clad laminate according to claim 1, characterized in that: Also includes: Solvent: 50-130 parts.

6. The adhesive for copper clad laminate according to claim 5, characterized in that: The solvent includes at least one of dimethylformamide, acetone, butanone, toluene, xylene, propylene glycol methyl ether, ethylene glycol methyl ether and cyclohexanone.

7. The method for preparing a glue for copper clad laminate according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: firstly, using a solvent with a mass of 5 to 10 times that of the curing agent to dissolve the curing agent; then adding 4-aminobenzoic acid phenol ester phthalonitrile and core-shell particles into the remaining solvent, stirring and mixing at 45 to 60 DEG C; then mixing with the main resin, stirring at high speed for 20 to 60 minutes until uniform; continuing to add the dissolved curing agent, stirring to make it uniformly mixed; then adding fillers, stirring and emulsifying at high speed for 30 to 60 minutes until uniform; finally adding an accelerator, stirring and emulsifying at high speed for 20 to 60 minutes until uniform; and maintaining the high-speed shearing emulsification stirring and maturing for 5 to 10 hours to complete the preparation.

8. A method for preparing a copper clad laminate, characterized in that: The following steps are involved: The glue liquid described in claims 1-6 is applied on the glass fiber cloth to form a glue layer with uniform thickness; then the glue liquid is dried to volatilize the solvent in the glue liquid to form a semi-cured sheet; and then the semi-cured sheet is compounded with copper foil and pressed to prepare a copper clad laminate.

9. The method for preparing a copper clad laminate according to claim 8, characterized in that: Gluing is done at 180-210°C at a speed of 10-30 m / min; The pressing is done at a pressure of 25-35 kg / cm 2 , press at a temperature of 170-190°C for 60-120 minutes.

10. A copper clad laminate, characterized in that: The compound is prepared by the preparation method according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Method for preparing copper-clad laminate by using polyphenylene oxide resin composition

    CN108263068A

  • Toughening-antiflaming type epoxy resin and preparation method thereof

    CN102850520A

  • High-temperature-resistant and flame-retardant epoxy resin and preparation method

    CN107663360A

  • Flame-retardant epoxy resin and preparation method thereof

    CN108794981A

  • Glue solution for primary color copper-clad plate as well as preparation method and application thereof

    CN112063114A